PEMEROLEHAN KALIMAT BAHASA INDONESIA PADA ANAK USIA 3 TAHUN DI KB YAA BUNAYYA SURABAYA - Luana Ardalia, Lintang; Ardhianti, Mimas (Universitas PGRI Adi Buana Surabaya, 2019)
The acquisition of Indonesian sentence on 3 years old children tend to be very simplethat describes the mindset, behavior, and personality to tell the events that happened thoughsometimes still not right and not yet become a complete sentence. The purpose of this study isto know and describe the acquisition of sentences in children aged 3 years in KB YaaBunayya Surabaya. In the form of declarative sentences, interrogative imperatives, andsentence solicitation. The method used in this research is descriptive qualitative researchmethod. technique of data collection using conversation involve gathering technique,recording technique, and record technique. The analytical techniques used are transcript thedata, recording, classifying, and retell. The result of this research is the acquisition ofdeclarative sentence of 3 years old child there are four kinds. In addition to the declarativesentence, there are also 3 interrogative sentences that are interrogative sentences thatrequire the recognition of